2013
DOI: 10.2147/ott.s44906
|View full text |Cite
|
Sign up to set email alerts
|

Glycoprotein non-metastatic b (GPNMB): A metastatic mediator and emerging therapeutic target in cancer

Abstract: Molecularly targeted therapies are rapidly growing with respect to their clinical development and impact on cancer treatment due to their highly selective anti-tumor action. However, many aggressive cancers such as triple-negative breast cancer (TNBC) currently lack well-defined therapeutic targets against which such agents can be developed. The identification of tumor-associated antigens and the generation of antibody drug-conjugates represent an emerging area of intense interest and growth in the field of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 103 publications
(181 reference statements)
2
68
0
Order By: Relevance
“…It is a heavily glycosylated protein with sites for both N- and O- glycosylation [12]. GPNMB is localized on the plasma membrane as well as in subcellular locations in various cell types.…”
Section: Gpnmb Structure and Functionmentioning
confidence: 99%
“…It is a heavily glycosylated protein with sites for both N- and O- glycosylation [12]. GPNMB is localized on the plasma membrane as well as in subcellular locations in various cell types.…”
Section: Gpnmb Structure and Functionmentioning
confidence: 99%
“…GPNMB is overexpressed on triple negative breast cancer, among other solid tumors[266]. A phase I/II clinical trial demonstrated that it is active in advanced melanoma[267].…”
Section: Antibodies As Targeting Vehiclesmentioning
confidence: 99%
“…A phase I/II clinical trial demonstrated that it is active in advanced melanoma[267]. Clinical data suggest that it is particularly active in triple negative breast cancer patients with high levels GPNMB expression[266]. Ongoing phase II studies will provide more information about its activity.…”
Section: Antibodies As Targeting Vehiclesmentioning
confidence: 99%
“…Glycoprotein non-metastatic b (GPNMB) is overexpressed in certain solid tumours, including triple-negative breast cancer and melanoma, and is the target for the immunoconjugate glembatumumab vedotin. 78 In a phase II study using glembatumumab vedotin, patients with metastatic, heavily pre-treated, breast cancer experienced a comparable overall survival to investigator’s choice of chemotherapy. 79 However, in the subset of patients with triple-negative breast cancer and high GPNMB expression, a statistically significant improvement in overall survival was observed with the use of glembatumumab vedotin over investigator’s choice of chemotherapy (10.0 months versus 5.5 months, P = 0.003).…”
Section: Immunoconjugate Therapeutic Entitiesmentioning
confidence: 99%